Fly girls [large type] : how five daring women defied all odds and made aviation history - O'Brien, Keith, 1973- (Thorndike Press, a part of Gale, a Cengage Company, 2018)
Between the World Wars, no sport was more popular or more dangerous than airplane racing. Male pilots were hailed as heroes, and female pilots were ridiculed for their efforts to break into the manly sport. O'Brien weaves together the stories of five female aviators, Florence Klingensmith, Ruth Elder, Amelia Earhart, Ruth Nichols and Louise Thaden, who fought for the chance to race against men in the high-stakes air races of the 1920s and 1930s. In 1936 Louise Thaden claimed the title of America's best pilot by winning the Bendix Trophy Race, beating her closest competitor (also a woman) by 45 minutes, and the closest man by 50 minutes.